Assesment of felodipine glass transition behaviour using modulted temperature differential scanning calorimetry - Zajc, Natalija (Acta chimica slovenica, 2002)
Glassy felodipine samples have been investigated thermoanalytically by means of modulated temperature differential scanning calorimetry (MTDSC). The methodadvantage of improved signal to noise ratio is confirmed and the glass transition is determined independently from the relaxation phenomena. Experiments with linear saw-tooth modulation with different xperimental parameters revealed the strong influence of the modulation period on the data derived. The activation energy of the felodipine glass transition is calculated, introducing different value as determined previously
Keywords: aktivacijska energija; felodipin; temperatura steklastega prehoda; termična analiza